A case of Prader-Willi Syndrome with Behavioural Disturbances: a successful multidisciplinary management approach - Md Rosli, Najwa Hanim; Md Tahir, Mohd Faiz (2020)
Prader-Willi Syndrome (PWS) is a genetically determined neurodevelopmental disorder occurring in 1 in 15,000 births. PWS is a rare case in Malaysia and a successful approach to its management has not been well reported here. We present a case of a 13-year-old boy with Prader-Willi Syndrome with prominent behavioural disturbances characterised by temper tantrums, compulsive food intake, stubbornness, stealing and impulsivity further complicated by underlying morbid obesity, poorly controlled type 2 diabetes mellitus, hypertension, dyslipidaemia, obstructive sleep apnoea syndrome and intellectual disability. Multidisciplinary approach involving child and adolescent psychiatrist, occupational therapist, counsellor, family therapist, endocrinologist and dietician has shown to improve the patient’s weight, glucose and blood pressure control and most importantly the behavioural disturbances.